The effect of employing different reading strategies on reading comprehension of EFL Libyan Students by using the Think-Aloud Protocol - Dr. Faisal Moftah Rajeb Khellab; Mrs. Arbia Saleh Salem Elghoul (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2024)
This study explored the reading strategies employed by upper- intermediate and advanced-level Libyan EFL learners. The purpose of this study is to find the most effective reading strategies used by Libyan EFL students for tackling the reading task and answering the test. Also, to study the effects of employing the think-aloud protocol on their reading performance, in this study, the think-aloud protocol was used. The investigation found that the advanced EFL learners were keen to use more strategies in their attempt to comprehend the texts at hand when compared to the upper-intermediate students. The lower-proficient students got stuck during the reading task and had to be helped and prompted to stay on track. They also employed strategies less frequently when compared with the advanced students. It is clear that as the student’s proficiency levels increased, so did their conscious use of strategies and confidence.